Hydrogeochemical modeling (KIRMAT) of spring and deep borehole water compositions in the small granitic Ringelbach catchment (Vosges Mountains, France). (December 2017) - Lucas, Y.; Chabaux, F.; Schaffhauser, T.; Fritz, B.; Ambroise, B.; Ackerer, J.; Clément, A.
Abstract: This study presents the results of the coupled hydrogeochemical modeling of the geochemical compositions of spring and borehole waters from the Ringelbach catchment, which is located in the Vosges Mountains (France). This site has been equipped with 150-m-deep boreholes, facilitating the sampling of both rock and groundwater in the granitic bedrock. The data point to very contrasting chemical compositions between spring and borehole waters, which are discussed and explained in this study by the application of the coupled hydrogeochemical code KIRMAT. Using hydrological and geochemical data, simulations were performed through two different water pathways, which crossed different types of rocks within the Ringelbach massif: a subsurface and fast (>2.5 mH2O .yr −1 ) water flow, which is more or less parallel to the slope, for waters supplying the springs, and a rather vertical and slower flow (0.5–0.1 mH2O .yr −1 ) for the borehole waters. The KIRMAT simulations make it possible to account for not only the geochemical differences between the spring and borehole waters but also the geochemical variations observed in waters in both contexts. For borehole waters, the model confirms the importance of the dissolution of minor mineralogical phases that are present in the granite (here, carbonates/dolomites) on the chemical budget of waters. It also shows that the chemical differences between the waters collected in the two studied boreholes result from differences in the water flow in the granitic bedrock, i.e., the difference between water flow in a regular porous medium and water flow in a porous medium crossed by a fracture. This result likely highlights the role of geological inheritance on the hydrodynamical rock properties and the chemical compositions of waters circulating within the granitic bedrock. For spring waters, this model enabled us to constrain the nature of the rock in the pathway, which is neither saprolite nor fresh granite but is instead weathered granite with a weathering age of several tens of thousands of years. Spatial and seasonal variations in the chemical compositions of spring water can be explained as the result of the same circulation pattern for which the water-rock interaction time is determined by the length of the pathway and the water velocity. Especially in cases in which this interaction time is long enough, the precipitation of clay phases is enabled, which plays a major role in determining the chemical composition of the water. Despite the only one-dimensional approach and the uncertainties linked to the geochemical complexity and the associated kinetic data, the results obtained in this study demonstrate the effectiveness of using coupled hydrogeochemical modeling to better understand and quantify the weathering processes and the coupling that exists between water circulation dynamics and water-rock interactions at the catchment scale. Highlights: Very contrasting chemical compositions between spring and borehole waters. Hydrogeochemical modeling enables to account for the geochemical differences. The model highlights the role of geological inheritance on the hydrodynamical rock properties. For spring waters, the model enables to constrain the nature of the rock in the pathway. Spatial/seasonal variations of spring water compositions explained as the result of the interaction time variations.